Horizon scanning for transport research and innovation governance: A European perspective. (September 2021) - Tsakalidis, Anastasios; Boelman, Elisa; Marmier, Alain; Gkoumas, Konstantinos; Pekar, Ferenc
Highlights: The paper describes a proof-of-concept horizon scanning to support forward-oriented transport R&I. Text mining combined with analyst intelligence retrieved potentially relevant weak signals. A transport-expert workshop assessed/clustered weak signals, to feed EU policy/decision-making. Flagged areas: urban car-replacement, electrification & power demand, fleet retrofit, automation. Signals of change affecting transport do not necessarily originate within the transport sector. Abstract: The European Commission's Transport Research and Innovation Monitoring and Information System (TRIMIS) is co-developed by the authors as an open-access transport policy tool to support implementation of the Strategic Transport Research and Innovation Agenda (STRIA), covering all transport sectors and modes. Within the TRIMIS frame, horizon scanning has been piloted through a structured and systematic collaborative exercise contributing to the identification of new and emerging technologies and trends. It focused especially on those affecting the transport sector, supporting the assessment of current and future research needs. This exercise also feeds broader European Commission policies with transport insights, thereby contributing to policy integration. The TRIMIS horizon scanning pilot shed light onto various emerging technologies that can potentially disrupt mobility and transport. It highlighed the significance of the interaction of the energy and transport sectors, and the need to invest in related research and innovation to address complex emerging challenges identified in the expert workshop: Radical solutions to replace cars in urban environments; Electrification and escalation of power demand; Fleet modernisation through retrofitting; and Automation to maintain current system with less externalities. This paper provides an overview of the role, application and outcomes of the horizon scanning methodology co-developed and piloted by the authors to support transport research and innovation in a European Union (EU) policy context.